The Role of Adult Attachment Style in Online Social Network Affect, Cognition, and Behavior - Rom, Eldad; Alfasi, Yitshak (Journal of Psychology and Psychotherapy Research, 2014)
In the last decade, social network sites (SNS) have a major attendance in our everyday lives. Numerous studies have explored the antecedences and consequences of this novel phenomenon. The current study is yet another attempt in this direction. In this research we seek to explore the role of personality tendencies, namely the attachment system, in individuals' affect, cognitions, and behavior on what is presently considered as the most popular SNS - "Facebook". Over the years studies have continuously demonstrated that attachment theory is a relevant framework for understanding human behavior and has proven attachment tendencies to be significantly associated with quality of close relationships and daily social interactions. Since today virtual communication and social networks are capturing dominant aspects of social relationships, the linkage to attachment theory is evident. Hence, we approached 190 Israeli young adults, and asked them about their habits and daily routines on Facebook. We also measured their cognition and emotion concerning Facebook. Results show that attachment insecurity is associated with global orientations and emotions towards Facebook and that people develop attachment relationships with their Facebook network. We discuss the associations between attachment and virtual communication and its application for future theory and research.